Eles não sabem o que não querem saber : a apropriação Zizekiana do conceito de “encarnação de Deus” de Hegel - Fabiano Veliq Barbosa (2023)
The present thesis aims to understand how the Slovenian philosopher Slavoj Žižek appropriates the concept of the incarnation of God elaborated by Hegel. To this end, we seek to highlight the importance of the concept of incarnation for the history of Christianity, as well as its appropriation and centrality for Christian theology. From this history of the concept of the incarnation of God, we were able to turn to the thought of the Slovenian philosopher Slavoj Žižek and find out how he understands the concept of incarnation to think about Christianity. The notion of the incarnation of God will be thought of by the philosopher in a literal way, so that in this reading Christianity would maintain at its core an atheistic proposal, as it would be the only religion in which God actually dies, since God, when incarnating, he would be emptying himself completely and fully assuming human nature. By focusing on Žižek's texts on the theme of religion, we were able to analyze how the concept of the incarnation of God and the themes of Hegel's philosophy of religion appeared in Žižek's work. At various times Žižek claims to rely on a Hegelian reading of the concept of incarnation and at this point we were able to perceive how the Žižek ian reading on the theme of incarnation in Hegel is fragile and several times mistaken and confused. When trying to rely on Hegelian formulations and also on the proposals of Freudian and Lacanian psychoanalysis, Hegel is left aside and primacy is given to Lacanian thought. Žižek's reading on the theme of the incarnation of God goes beyond the merely theological sense, as the Slovenian philosopher sees Christianity as a strong discourse that sustains much of the Western worldview, and for that reason he seeks to emphasize the analysis and criticism of religion. Christian. However, Žižek's reading on the theme of incarnation raises several problems, mainly in relation to theological issues on which Žižek seeks to base his proposal on Christianity, and because he tries to base his proposal on Hegelian philosophy, he fails to make a reading that matches with the proposal of the German philosopher on the theme of the incarnation.